Hvad er et teaterkompagni? Det irske eksempel - Edelman, Joshua (Peripeti, 2009)
When describing a cultural field sociologically, it is essential to know the identity of the actors within it. For the theatre, these are the companies that make the work. But exactly what a theatre company is varies enormously between countries. This article looks at the Irish example, in which the theatre company is more of a brand than a stable organizational entity. The article examines the effects this structure has on the field as a whole in terms of the concepts of niche and autonomy.